2021
DOI: 10.1186/s12966-020-01077-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants related to physical activity or sedentary behaviour: a systematic review

Abstract: Background Research shows that part of the variation in physical activity and sedentary behaviour may be explained by genetic factors. Identifying genetic variants associated with physical activity and sedentary behaviour can improve causal inference in physical activity research. The aim of this systematic review was to provide an updated overview of the evidence of genetic variants associated with physical activity or sedentary behaviour. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 98 publications
(140 reference statements)
0
17
0
Order By: Relevance
“…Exercise has powerful effects on neurobiological processes such as neurotransmission, cognition, and reward-dependent behaviors (Rhodes et al 2005 ; Caetano-Anolles et al 2016 ; Saul et al 2017 ). While motivation and physiological ability are critical determinants of an individual’s physical activity levels (Garland et al 2017 ), long-term genetic selection experiments in laboratory mice have also illuminated genes associated with elevated levels of voluntary exercise (Kelly et al 2012 ; Kostrzewa and Kas 2014 ; Vellers et al 2018 ; Aasdahl et al 2021 ). RNA (Zhang et al 2018 ) and whole genome (Xu and Garland 2017 ; Hillis et al 2020 ) sequencing from mice selected for elevated physical activity levels have revealed differential expression of genes associated with behavior, motivation, and athletic ability, supporting a genetic basis for elevated physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise has powerful effects on neurobiological processes such as neurotransmission, cognition, and reward-dependent behaviors (Rhodes et al 2005 ; Caetano-Anolles et al 2016 ; Saul et al 2017 ). While motivation and physiological ability are critical determinants of an individual’s physical activity levels (Garland et al 2017 ), long-term genetic selection experiments in laboratory mice have also illuminated genes associated with elevated levels of voluntary exercise (Kelly et al 2012 ; Kostrzewa and Kas 2014 ; Vellers et al 2018 ; Aasdahl et al 2021 ). RNA (Zhang et al 2018 ) and whole genome (Xu and Garland 2017 ; Hillis et al 2020 ) sequencing from mice selected for elevated physical activity levels have revealed differential expression of genes associated with behavior, motivation, and athletic ability, supporting a genetic basis for elevated physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…The precise underlying molecular mechanisms behind these physiological changes remain poorly characterised. It is clear that individual’s inherited genetic variants, epigenetic makeup, and the resultant regulation of gene expression, impacts of PA and PA-related phenotypes as well as the ageing process [ 2 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors may explain different degrees of variance in physical activity depending on sex 54 and activity duration 55 . GWAS and candidate gene studies have also identified specific genomic loci implicated in physical activity, with a recent GWAS conducted in the UK Biobank identifying 14 independent loci and gene pathways enriched in neurological disease, brain structure, and cognitive function 52,[56][57][58] .…”
Section: Genetic Associations Of Physical Activitymentioning
confidence: 99%